Strategi komunikasi BPJS Ketenagakerjaan dalam implementasi program jaminan kehilangan pekerjaan (Studi kasus: BPJS Ketenagakerjaan Wilayah Sumatera Barat) - Alfiansa, Nicko; Nurjanah, Nurjanah; Yasir, Yasir (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The COVID-19 pandemic triggered the Large-Scale Social Restrictions (PSBB) policy which had a significant impact on the employment sector in Indonesia, including the high number of Termination of Employment (PHK). In response, the government through BPJS Employment launched the Job Loss Guarantee (JKP) program in 2021 to provide protection for affected workers. This research aims to analyze BPJS Employment's communication strategy in socializing the JKP program in West Sumatra, which recorded a high number of informal workers (61.64%) and low BPJS Employment participation. The research results show that the communication strategy is not optimal due to limited promotional media and the lack of information received by the company and the public. Research recommendations emphasize the importance of implementing two-way communication, increasing the intensity of outreach through print and electronic media, and collaborating with community leaders to reach the informal segment. This strategy is expected to increase public understanding and effectiveness of the implementation of the JKP program